Broadcasting algorithm based on successful broadcasting ratio and energy balance of nodes in mobile ad hoc networks. (2018) - Yu, Yanping; Li, Long; Liu, Keyan; Deng, Yichen; Su, Xue
Blind flooding in mobile ad hoc networks could result in the broadcast storm problem and the broadcast unreliability. To mitigate the broadcast storm, improve the broadcasting reliability and prolong the lifetime of networks, we propose a broadcasting algorithm based on successful broadcasting ratio and energy balance of nodes (BSREB) in mobile ad hoc networks. Heavy traffic usually aggravates the broadcast problem. Thus, we introduce the successful broadcasting ratio which reflects both local topology and traffic to determine the forwarding probability. To prolong the network lifetime, energy balance strategy is adopted by using residual energy to determine the forwarding probability. Since the forwarding probability of each node is determined by its own successful broadcasting ratio and residual energy, BSREB is simple and easy to implement. The simulation results show that BSREB can achieve a lower latency and higher reachability. Meanwhile, the BSREB algorithm has a strong adaptability to node mobility.